THE USE OF DIALOGUE JOURNALS ACTIVITY IN ESSAY WRITING COURSE (STUDENTS’ ACHIEVEMENT) - Hidayah Nor (IAIN Syekh Nurjati Cirebon, 2017)
This research is aimed to describe the use of dialogue journals technique in improving students’ writing skill especially students’ achievement in short essay writing course. The researcher used descriptive qualitative research for conducting the research. The subjects of this research were the fifth semester students of English Education Department academic year 2016-2017 and there were two classes which involving 65 students. The instruments that were used to get the data are the writing test in form of essay. It is considered valid based on the view of test content and the representation of the materials tested since the test uses content validity. Then, all the data were analyzed descriptive qualitatively and concluded inductively. The result of this research was to provide English lecturers with interesting and effective teaching strategies in enhancing the students’ active participation in teaching and learning process and improving students’ writing ability. The students were expected to use dialogue journals activity to improve their ability in writing. This research also gave additional value to the effort of increasing the quality of teaching English particularly teaching writing in Indonesia.